Ekvira Devi - Mumbai Archive Project Team (Jio Institute, 2024)
Ekvira Devi considered a form of the Goddess Renuka, is revered as the kuladevi (family deity) of the Koli community. Each year, Kolis embark on pilgrimages to offer prayers to Ekvira Devi at her temple located at the Karla Caves.